Five Islands, Trinidad, B.W.I. (Stephens Ltd., Trinidad, 2011)
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided The postcard shows the "Five Islands" which are actually a group of six islands that are located west of Port of Spain, the capital of Trinidad, in the Gulf of Paria. The six islands are: Caledonia Island, Craig Island, Lenagan Island, Nelson Island, Pelican Island and Rock Island. They are also known as Las Cotorras. Funding for this project has been provided by Mrs. Irma E. Goldstraw.